Efek Media Slide dan Media Sosial terhadap Pengetahuan HIV/AIDS dan VCT (Voluntary Counseling and Testing) pada Pekerja PT. X di Kabupaten Tabalong - Astuti, Henni Widia; Rezeki Sudarmin, Ria; Hairuddin, Hairuddin; Meiliani Yulis, Dian; Herman, Sriyana (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
This study aims to analyze the effectiveness of health promotion media, namely slide media and social media (animated videos), in improving workers' knowledge and interest in HIV/AIDS and Voluntary Counseling and Testing (VCT) at PT. X, Tabalong Regency, South Kalimantan. The study utilized a quasi-experimental design with a two-group pre-posttest method, involving 360 respondents. Group A received counseling using slide media, while Group B was educated through animated videos shared via WhatsApp. The results showed a significant increase in knowledge in both groups, with the slide media group demonstrating higher effectiveness compared to the social media group (p < 0.001). However, interest in VCT did not show a significant relationship with increased knowledge in either group (p > 0.05). Slide media proved to be more effective than social media in enhancing workers' knowledge of HIV/AIDS. These findings highlight the importance of using appropriate health promotion media to educate workers about health issues.